Sustainability accounting and the philosophy of Baudrillard and Foucault: The movement from representation to disciplinary power - Bima Rafly Fachrezzi (Environmental, Social, Governance and Sustainable Business, 2026)
Background: This study critically examines sustainability accounting through the philosophical perspectives of Baudrillard and Foucault, highlighting a shift from representation to disciplinary power. While sustainability accounting is commonly perceived as a neutral mechanism for representing environmental and social realities, this study argues that it increasingly operates within a regime of simulation and control. Methods: Using a qualitative critical-theoretical approach grounded in Critical Discourse Analysis (CDA), this study analyzes key global sustainability frameworks and reports as discursive artefacts. Findings: The findings reveal that sustainability accounting constructs hyperreal representations of ecological reality, where ESG disclosures function as simulacra that obscure material environmental conditions. Furthermore, through a Foucauldian lens, sustainability accounting operates as a disciplinary technology that normalizes corporate behavior through mechanisms of visibility, standardization, and evaluation. As a result, organizations are driven to perform sustainability rather than substantively practice it. Conclusion: The study concludes that sustainability accounting should be understood not merely as a representational tool, but as a form of power that shapes knowledge, behavior, and moral expectations within global governance systems. Novelty/Originality of this article: This research contributes to the critical accounting literature by offering an integrated philosophical critique that repositions sustainability accounting as both a symbolic and disciplinary apparatus.